Hemispheric asymmetry of motor cortex excitability in mood disorders – Evidence from a systematic review and meta-analysis - Cotovio, Gonçalo (2022)
Funding Information: Funding: GC was supported by Fundação para a Ciência e Tecnologia (FCT) through a PhD Scholarship (SFRH/BD/130210/2017). AJO-M is supported by grant FCT-PTDC/MEC-PSQ/30302/2017-IC&DT-LIS BOA-01-0145-FEDER, funded by national funds from FCT/MCTES and co-funded by FEDER, under the Partnership Agreement Lisboa 2020 - Programa Operacional Regional de Lisboa. GC and AJO-M are supported by grant FCT-PTDC/MED-NEU/31331/2017, funded by FCT/MCTES. This project was funded by the European Union’s Horizon 2020 research and innovation programme under grant agreement No 777167. AJO-M was national coordinator for Portugal of a noninterventional study (EDMS-ERI-143085581, 4.0) to characterize a Treatment-Resistant Depression Cohort in Europe, sponsored by Janssen-Cilag, Ltd (2019–2020), is recipient of a grant from Schuhfried GmBH for norming and validation of cognitive tests, and is national coordinator for Portugal of trials of psilocybin therapy for treatment-resistant depression, sponsored by Compass Pathways, Ltd (EudraCT number 2017-003288-36 and 2020-001348- 25), and of esketamine for treatment-resistant depression, sponsored by Janssen-Cilag, Ltd (EudraCT NUMBER: 2019-002992-33).